Inhibition of the Biofilm Formation of Plant Streptococcus mutans - Atazhanova, G.A.; Levaya, Y.K.; Badekova, K.Zh.; Ishmuratova, M.Yu.; Smagulov, M.K.; Ospanova, Zh.O.; Smagulova, E.M. (Pharmaceuticals, 2024)
This review is devoted to a systematic analysis of studies aimed at investigating plant extracts, essential oils and phytochemical compounds capable of inhibiting Streptococcus mutans biofilm formation. This paper investigates the effect of extracts, essential oils and individual plant compounds on inhibiting the biofilm formation of Streptococcus mutans, one of the major pathogens responsible for the development of dental caries. Using cultural microbiology and molecular biology techniques, the authors describe the mechanisms by which plant samples reduce Streptococcus mutans adhesion and growth. The results show that several plant components have antibacterial properties, contributing to the reduction of Streptococcus mutans colony numbers and inhibiting the synthesis of extract-exopolysaccharide matrices required for biofilm formation. This work highlights the potential of botanicals in inhibiting Streptococcus mutans biofilm formation, which can be applied as natural antimicrobial agents in the prevention and treatment of dental diseases. Views on the use of these plant extracts and their components in dental preparations such as toothpastes, rinses and gels aimed at preventing dental caries are evaluated. The review shows the relevance of the research to optimizing the use of plant extracts, essential oils, individual compounds and their active actions in the control of Streptococcus mutans biofilms.
Keywords: biofilm formation; Streptococcus mutans; plants; dental caries; microbial ecology